Paediatric HERMES: European accreditation of training centres in paediatric respiratory medicine. Issue 2 (June 2016) - Sutter, Sandy; Mitchell, Sharon; Eber, Ernst; Hedlin, Gunilla; Midulla, Fabio; Niculescu, Alexandra; Paton, Jimmy Y.; Ross-Russel, Robert; Gappa, Monica
Some form of medical training accreditation is used in over 110 countries worldwide [1 ]. Although accreditation criteria and processes vary considerably depending on regional medical training structures and national regulations, various studies suggest that the accreditation of training programmes has a positive impact on trainees' performance in assessments [2, 3 ]. Thus, accreditation is an important tool for promoting high-quality training and medical care. HERMES: European accreditation of training centres in paediatric respiratory medicine http://ow.ly/ZBmUg